Impact of preoperative chemotherapy on the histological response of patients with peritoneal metastases from colorectal cancer according to peritoneal regression grading score (PRGS) and TRG. (June 2020) - Taibi, Abdelkader; Lo Dico, Rea; Kaci, Rachid; Naneix, Anne Laure; Mathonnet, Muriel; Pocard, Marc
Abstract: Background: This study evaluated the histologic response after preoperative systemic therapy (pST) using the Peritoneal Regression Grading Score (PRGS) and tumor regression grade (TRG) classifications for patients with peritoneal metastases (PM) from colorectal cancer (CRC). Methods: Twenty-three patients were selected from a prospective database of 196 patients who underwent CRS followed by HIPEC for synchronous PM from CRC. In all study patients, biopsies of the PM obtained before pST (during the first laparoscopy) and after pST (during cytoreductive surgery) were compared. Results: Complete (PRGS 1), Major (PRGS 2), Minor (PRGS 3) and no histological responses (PRGS 4) were obtained in 17, 5%, 52% and 13% and 17, 5% of patients, respectively. Major (TRG 1–2), partial (TRG3), and no (TRG4-5) histological tumor regression were observed in 61%, 9% and 30% of patients, respectively. Regardless of the classification applied, median OS was significantly higher in patients with a "complete or major" response than in those with a "minor/partial or no" response (54 vs. 26 months, p < 0.05). Conclusions: The PRGS and TRG can be used in clinical practice to evaluate the histological response after pST. This study demonstrated that a complete histologic response of PM from CRC can be obtained after pST. Highlights: Pathologic assessment plays a central role in patient management. Complete histological response has been associated with a favourable clinical outcome. The PRGS and TRG can be used in clinical practice after pST. Abstract : This study evaluated the histological response of peritoneal metastases from colorectal cancer after preoperative systemic therapy. The results demonstrated that complete histological tumour regression can be obtained with preoperative systemic chemotherapy and is a prognostic factor.